Analisis Pendekatan Teks dan Konteks dalam Hukum Islam tentang Kasus Korupsi - Abdulloh Munir (Al-Mizan (e-Journal), 2017)
This study discusses the problem of corruption that occurs in society. This study uses a textual approach and context in Islamic law. The results of the study show that: First, the nature of corruption is an act which all leads to evil, unrighteousness, fraud, injustice which consequently will damage and result in the destruction of the order of life of the family, society, nation and state; Secondly, the Qur'an and hadith mention corruption with several terms, such as: embezzlement, bribery, robbery, theft, and seizure; Third, sanctions for corruptors in the text and context of Islamic law are the death penalty, the law of cutting off hands, being crucified, crossing arms and legs crossing, being exiled and imprisoned.